PAULO FREIRE AND THE PEDAGOGICAL USE OF VISUAL IMAGE IN LITERACY OF YOUTH AND ADULTS - Carlos, Erenildo João (2017)
This test performs two functions. The first is to analyze the order of discourse that makes use of the image emerge in the literacy process present in the Freirean pedagogical proposal. The second, while working with the theoretical-methodological approach of the Archaeological Analysis of Discourse - AAD, proposed by Michel Foucault, seeks to affirm that the AAD is characterized as a possibility of investigation in the field of education and, specifically, of popular education. We find that the statement of the pedagogical use of the image appears in mentions about the genres of drawing, pictorial, photographic and audiovisual. The use of visual images is related to the notions of visual code, representation of the world and object of knowledge; And the functions mnemonic association, illustration and mediation of knowledge as pedagogical strategies of the literacy of young people and adults. The study points out, on the one hand, the theoretical and methodological pertinence of the DAF, on the other hand, that although Freire did not develop an elaborate discussion, the problem of the visual image has not ceased to be the object of its attention and use in educational practice.